Thermal Activation of Thin Filaments in Striated Muscle - Ishii, Shuya; Oyama, Kotaro; Shintani, Seine A.; Kobirumaki-Shimozawa, Fuyu; Ishiwata, Shin’ichi; Fukuda, Norio (Frontiers in Physiology, 2020)
In skeletal and cardiac muscles, contraction is triggered by an increase in the intracellular Ca2+ concentration. During Ca2+ transients, Ca2+-binding to troponin C shifts the “on–off” equilibrium of the thin filament state toward the “on” sate, promoting actomyosin interaction. Likewise, recent studies have revealed that the thin filament state is under the influence of temperature; viz., an increase in temperature increases active force production. In this short review, we discuss the effects of temperature on the contractile performance of mammalian striated muscle at/around body temperature, focusing especially on the temperature-dependent shift of the “on–off” equilibrium of the thin filament state.